Together we re still strong - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Cooperatives and poverty alleviation By J A Banturaki, Tema Publishers, 2000. 160 pp. ISBN 9987250227 GBP 8.95 Euro 14.40